Prevalence of dental anomalies of number in different subphenotypes of isolated cleft palate - João Paulo Schwartz; Daniele Salazar Somensi; Priscila Yoshizaki; Luciana Laís Savero Reis; Rita de Cássia Moura Carvalho Lauris; Omar Gabriel da Silva Filho; Gisele Dalbén; Daniela Gamba Garib (Dental Press Editora, 2014)
OBJECTIVE: This study aimed at carrying out a radiographic analysis on the prevalence of dental anomalies of number (agenesis and supernumerary teeth) in permanent dentition, in different subphenotypes of isolated cleft palate pre-adolescent patients. METHODS: Panoramic radiographs of 300 patients aged between 9 and 12 years, with cleft palate and enrolled in a single treatment center, were retrospectively analyzed. The sample was divided into two groups according to the extension/severity of the cleft palate: complete and incomplete . The chi-square test was used for intergroup comparison regarding the prevalence of the investigated dental anomalies (P < 0.05). RESULTS: Agenesis was found in 34.14% of patients with complete cleft palate and in 30.27% of patients with incomplete cleft palate. Supernumerary teeth were found in 2.43% of patients with complete cleft palate and in 0.91% of patients with incomplete cleft palate. No statistically significant difference was found between groups with regard to the prevalence of agenesis and supernumerary teeth. There was no difference in cleft prevalence between genders within each study group. CONCLUSION: The prevalence of dental anomalies of number in pre-adolescents with cleft palate was higher than that reported for the general population. The severity of cleft palate did not seem to be associated with the prevalence of dental anomalies of number.